Situs Percandian Batujaya di Karawang Jawa Barat: Analisis Manajemen Sumber Daya Arkeologi - Mustafa Mansur (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2015)
This paper seeks to present the existence and preservation of the temple siteUnur Jiwa, Lempeng, and Blondongan in Batu Jaya Karawang - West Java asarchaeological resources. The method used in this study is the observation andstudy literature, using the concept of archaeological resource management. Theaim of this study is to see how the existence and preservation of these sites, aswell as the principle of benefit of preservation. The study shows that thepresence of the sites related to Hinduism and Buddhism eksistensii intoIndonesia in the 4th century AD to 16th century AD, where temples were madeas a means of worship of the two religions. The use of temples that date havebeen preserved and utilized based on the potential ecological, architectonic,historical, and geological, besides the scientific research, creative arts,education, recreation and tourism, symbolic representation, legitimation ofaction, social solidarity and integration, and monetary and economic gain.